Development of Preliminary Criteria of Macrophage Activation Syndrome in Multisystem Inflammatory Syndrome Associated with COVID-19 in Children - Ilia S. Avrusin; Liudmila V. Bregel; Olesya S. Efremova; Mikhail M. Kostik (Biomedicines)
Background: Macrophage activation syndrome (MAS) can be regarded as a key factor determining the severity of multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C), and often requires treatment in the intensive care unit (ICU) to avoid life-threatening complications. No reputable specific criteria for the diagnosis of MAS in MIS-C patients have yet been identified, and criteria currently used for the diagnosis of hemophagocytic syndromes, such as HLH-2004, MAS-2005, and MAS-2016, are not sufficient for MAS in MIS-C. Our goal in this study was to work out the criteria for the early diagnosis of MAS in MIS-C. Methods: One hundred and sixty-six (166) patients with MIS-C were assessed retrospectively. The two most experienced experts independently identified patients with MAS. The patients were divided into three cohorts: MAS (n = 19), without MAS (n = 78), and probable MAS (n = 67). The latter included patients diagnosed with MAS by only one expert, and it was excluded from the analysis. Results: The age of patients with MAS was much higher, and they more frequently had edematous syndrome, hypotension and/or shock, splenomegaly, and CNS involvement. In their blood tests, thrombocytopenia, hypoalbuminemia, and hypertriglyceridemia occurred more often. The level of biomarkers of inflammation, such as ferritin, CRP, troponin, AST, and ALT, was also higher in this group. Increased fibrinogen and D-dimer were also found, demonstrating hypercoagulation in the MAS-MIS-C group. We chose 21 continuous and categorical variables with statistical significance, out of which 2—ferritin > 469 μg/L or platelets < 114 × 109/L—allowed us to discriminate MAS patients. Conclusions: Ferritin > 469 μg/L or platelets < 114 × 109/L can be regarded as key signs to differentiate MAS in MIS-C patients with a sensitivity of 100% and specificity of 94.9%, and they can be used along with other diagnostic methods.